The Metabolite of γ-Tocopherol, 2,7,8-Trimethyl-2-(2′-Carboxyethyl)-6-Hydroxychroman, Exerts Intracellular Antioxidant Activity via Up-Regulation of Heme Oxygenase-1 in Hepatocytes - Shosuke Aoyama; Tomoka Nishio; Daiki Moriya; Shintaro Munemasa; Yoshiyuki Murata; Yoshimasa Nakamura; Toshiyuki Nakamura (Nutraceuticals)
γ-Tocopherol (γT) is the major form of vitamin E contained in plants and seed oils. Although it is readily metabolized in the liver, the function of the metabolites is not fully understood. This study investigated the antioxidant activities of the γT metabolite 2,7,8-trimethyl-2-(2′-carboxyethyl)-6-hydroxychroman (γCEHC) in comparison to its parent compound. The pretreatment of mouse hepatoma Hepa1c1c7 cells with γCEHC showed a cytoprotective effect on the hydrogen peroxide-induced cytotoxicity to a lesser extent than that of γT. A mechanistic investigation revealed that both γ-CEHC and γT significantly up-regulated the gene and protein expressions of heme oxygenase-1 (HO-1) via the promotion of the nuclear translocation of nuclear factor erythroid 2-related factor 2 (Nrf2). Furthermore, the combination of γCEHC and γT significantly increased the gene and protein levels of HO-1 and the nuclear translocation of Nrf2, suggesting that it was an additive effect. Tin protoporphyrin IX (SnPP), a representative HO-1 inhibitor, significantly impaired the cytoprotection of γCEHC and γT against the hydrogen peroxide-induced cytotoxicity. These results suggested that not only γT but also its metabolite, γCEHC, are a promising cytoprotective factor against oxidative stress-induced cytotoxicity and that the cytoprotective effect is attributable to the cooperation of both compounds.